2023
DOI: 10.5829/ije.2023.36.09c.05
|View full text |Cite
|
Sign up to set email alerts
|

Decimal to Excess-3 and Excess-3 to Decimal Code Converters in QCA Nanotechnology

Abstract: Nowadays Quantum-dot Cellular Automata (QCA) is one of the new technologies in nanoscale which can be used in future circuits. Most digital circuits are implemented with CMOS technology, but CMOS has some problems like power consumption and circuit size. So, for solving these problems a new method (QCA) is presented. It is clear that converters play a crucial role in the digital world. So, due to the aforementioned point, in this paper, two digital code converters, containing an excess-3 to decimal, and a deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The recessed gate design further enhances the reduction of short-channel effects by allowing better control over the gate-tochannel distance. Short-channel effects, such as draininduced barrier lowering (DIBL) and subthreshold slope degradation, are minimized, leading to improved device performance for short-channel lengths [28]. The reduced lateral electric field in combination with precise gate control results in better subthreshold characteristics and improved transistor behavior.…”
Section: Lateral Electric Fieldmentioning
confidence: 99%
“…The recessed gate design further enhances the reduction of short-channel effects by allowing better control over the gate-tochannel distance. Short-channel effects, such as draininduced barrier lowering (DIBL) and subthreshold slope degradation, are minimized, leading to improved device performance for short-channel lengths [28]. The reduced lateral electric field in combination with precise gate control results in better subthreshold characteristics and improved transistor behavior.…”
Section: Lateral Electric Fieldmentioning
confidence: 99%
“…These findings revealed that the ON drain current increases linearly as temperature rises, whereas the drain OFF current rises exponentially as temperature rises. The primary electrical factors that govern the transistor's properties in analogue or digital circuits, such as ION /IOFF ratio, drain induced barrier lowering (DIBL), and VT, are all affected by the transistor's working temperature dependent characteristics as shown in Figure 11 [32].…”
Section: Analog Characteristicsmentioning
confidence: 99%